REFORMING THE INSTITUTE OF SALE OF DEBTOR'S PROPERTY IN BANKRUPTCY CASE - Козирєва, Валентина Петрівна; Бойко, Олексій Олегович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article is devoted to the analysis of the new Institute of Economic Law of Ukraine - the sale of property of the debtor in the bankruptcy case. The Institute of Electronic Bidding and the problem of litigation concerning the sale of debtor's property at auctions are analyzed. Research methods: analysis and synthesis, the dialectical method, statistical method. Results: identification of ways to improve the regulatory fixing of the sale of the debtor's property, sale of the arrested real estate through electronic auction. Discussion: issues of domestic law and practice related to the sale of property arising from the settlement of bankruptcy case. The article deals with the problems that arise in the process of foreclosure in the course of applying enforcement measures, which have become the main problem for many participants in the economic process. In bankruptcy proceedings, there are facts where the arbitration manager improperly fulfills the obligations of the liquidator without first agreeing with the creditors' committee the nomination of the subject of the valuation activity, which resulted in the reduction of the bankruptcy property value from the previous valuation. In view of the established, the courts concluded that the creditors' committee did not fully exercise its powers and did not determine any other way of valuation of property other than the expert evaluation, which was carried out by the debtor's liquidator following the procedure of bankruptcy legislation. We consider it expedient to make an addition to Art. 12 of the Bankruptcy Code of Ukraine, namely to supplement it with p.3.1 p.3 part 2, where to specify the duty of the arbitration manager on the basis of financial market analysis to evaluate the property and to specify the price of the lot, agreeing it with the committee of creditors and / or secured lender.